Alcohol septal ablation markedly reduces energy loss in hypertrophic cardiomyopathy with left ventricular outflow tract obstruction: A four-dimensional flow cardiac magnetic resonance study - Zhehao Dai; Nobuo Iguchi; Itaru Takamisawa; Morimasa Takayama; Mamoru Nanasato; Mitsuru Kanisawa; Naokazu Mizuno; Shohei Miyazaki; Mitsuaki Isobe (International Journal of Cardiology: Heart & Vasculature, 2021)
Background: Functional follow-up modalities of hypertrophic cardiomyopathy (HCM) with left ventricular (LV) outflow tract obstruction (LVOTO) subjected to alcohol septal ablation (ASA) are limited. Methods: This retrospective cohort study included patients of HCM with LVOTO who underwent ASA and four-dimensional (4D) flow cardiac magnetic resonance imaging (MRI) both before and after ASA. We analyzed energy loss in one cardiac cycle within the three-chamber plane of the LV and aortic root, and compared between pre- and post-ASA measurements. Results: Of the 26 included patients, 10 (39%) were male, and median age was 71 (interquartile range 58–78) years. ASA significantly reduced not only LVOT pressure gradient (70 [19–50] to 9 [3–16], P < 0.001), but also energy loss during one cardiac cycle within the three-chamber plane of the LV and aortic root (80 [65–99] to 56 [45–70], P < 0.001). A linear association was observed between the reductions of energy loss and pressure gradient (R2 = 0.58, P < 0.001). Conclusions: ASA significantly reduced energy loss within the LV and aortic root as quantified by 4D flow MRI, reflecting the decreased cardiac workload. This approach is a promising candidate for serial functional follow-up in patients undergoing ASA.